Modulation of Fire Regimes by Vegetation and Site Type in Southwestern Patagonia Since 13 ka - Moreno, Patricio I.; Vilanova, Isabel; Villa-Martínez, Rodrigo P.; Francois, Jean P. (Frontiers in Ecology and Evolution, 2018)
The degree to which vegetation and site type have influenced fire regimes through the Holocene has not been investigated in detail in the temperate ecosystems of southern Patagonia. Here we present a first attempt using a paired-basin approach to study the evolution of fire regimes in sectors dominated by humid Nothofagus forests and the xeric Patagonian steppe in the Magallanes region of Chilean Patagonia (51°S). We analysed sediment cores from two small lakes and a bog located within the same climate zone on opposite sides of the forest-steppe ecotone, 28 km apart. The position of this biological boundary east of the Andes is controlled by the strength and position of the southern westerly winds, which constitute the sole source of precipitation throughout western Patagonia. Our results indicate that fires have occurred in the study region repeated times over the last 13,000 years at bi- and tridecadal timescales. Sectors currently dominated by Patagonian steppe feature high frequency and low magnitude of local fires, and vice versa in humid forests. Climate-driven expansion of Nothofagus scrubland/woodland into steppe environments over the last 4200 years increased the magnitude and lowered the frequency of fire events, culminating with peak Nothofagus abundance, fire magnitude and frequency during the last millennium. We also detect divergences between lake-based versus bog-based paleofire histories among paired sites located within the Patagonian steppe, 12 km apart, which we attribute to local burning of the bog at times of lowered water table. This divergence suggests to us that bog-based vegetation and fire histories exacerbate a local, azonal, signal blurring extra-local or regional regimes, thus accounting for some discrepancies in the Quaternary paleovegetation/paleoclimate literature of southern Patagonia.